A pilot-plant investigation of a kinetic model for flotation - R. P. King (The Southern African Institute of Mining and Metallurgy, 1978)
The flotation behaviour of phoscorite from the Phosphate Development Corporation was measured in a pilot plant, the flotation cells in the plant being varied in configuration so as to operate with or without circulating loads. The ore was floated in a batch cell so that the parameters for a kinetic model could be estimated, and these parameters were then used in a flotation-plant simulator, which is based on the kinetic model, in the prediction of the performance of a pilot flotation plant operating on phoscorite. The simulator predictions compare well with the measured performance of the ore in the pilot plant, but the comparison shows that the kinetic model is not completely adequate for the prediction of performance in continuous flotation plants. The model is weakest in its ability to model the behaviour of the froth phase. The flotation behaviour of the ore could be adequately described when it was assumed that the apatite and gangue each consist of floatable and unfloatable components. The effect of particle size on the specific flotation-rate constant of apatite was found to have a maximum at 85 µm and to fall to zero at 400 µm that for the gangue had a maximum at 50 µm and was zero at 350 µm.